PENGARUH KECERDASAN EMOSIONAL GURU, KARAKTERISTIK PEKERJAAN DAN KEMATANGAN EMOSI TERHADAP KINERJA GURU DI MADRASAH TSNAWIYAH NEGERI 3 KABUPATEN SIMALUNGUN - Dedi Kuswadi; Getty Situmorang; Layla Ramadhani; Muhammad Ihsan; Watnika Purnama Sari (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The problem formulation of this research is how the influence of teacher emotional intelligence on teacher performance. How the characteristics of the work affect the performance of teachers. How emotional maturity affects teacher performance. How the teacher's emotional intelligence, work characteristics and emotional maturity affect the teacher's performance. The purpose of this study was to find out the influence of teacher's emotional intelligence on teacher performance. To find out the effect of work characteristics on teacher performance. To know the effect of emotional maturity on teacher performance. To find out the influence of the teacher's emotional intelligence, work characteristics and emotional maturity on the teacher's performance. The sample in this study amounted to 39 teachers. The data analysis techniques used in this study are descriptive analysis and multiple linear regression analysis. The results of this study explain that the variables of the teacher's emotional intelligence have a positive and significant effect on the teacher's performance. The variable characteristics of the work have a positive and significant effect on the teacher's performance. Variable emotional maturity has a positive and significant effect on teacher performance. The teacher's emotional intelligence variables, work characteristics and emotional maturity have a positive and significant effect on the teacher's performance.